Organic coffee cooperativism, fair trade and State: the promises still unfulfilled in the sustainabilityof the Peruvian Amazon - Chávez Achong, Julio (2023)
The possibility of coffee farming in the Peruvian Amazon to transform in a sustainable production, has as a condition that it alters the forest to a limited extent and, as far as possible, that it regenerates its ecological functions. For this purpose, it is essential not only to have laws and norms but mainly the determination of social actors to develop in this way when solving practical problems. This research aims to understand the behavior of the main actors, especially organic coffee cooperatives in their interaction with the State and fair-trade organizations in the Perene basin, in the central forest. The research was carried out in a specific situation: a critical phytosanitary juncture caused by the coffee yellow rust fungus (Hemileia vastatrix), in the second decade of this century. It analyzes data from a representative survey, interviews with multiple actors and secondary information.  The result, shows that, even when the cooperatives coffee production has certifications according to organic and fair-trade rules (and associate their crops with trees from the inga family), some of the partners reproduce deforestation trends affecting sustainability.